Obrona życia ludzkiego jako kwestia prawego sumienia - Wanat, Zbigniew (Teologia i Moralność, 2017)
One of the most important manifestations and signs of the new culture of life is unconditional defense of human life from conception to natural death which John Paul II spoke very often about. Involvement and forms of activity in this field depend on the state of human consciences - from their righteousness. The author shows this fundamental issue in the light of the remains current and relevant today Encyclical Evangelium vitae. At the beginning it refers to the fact that the word conscience is today a commonly used as a moral category, but ambiguously understood. He draws attention that the root of this phenomenon is on the one hand, the practical abandonment of the objective truth known by reason, and, on the other hand, the departure from the faithful revelations of the truths revealed by God. Then he shows his commitment to defending human life as a testimony of right conscience. He stops by the legal protection of human life from conception, indicates to verbal manipulations blurring the truth about actions against human life, and stresses the importance of opposing conscience to unjust law. Finally, he draws the issue of shaping the right conscience in the defense of human life. He indicates to the proclamation of the Gospel of life, at the center of which is the person of Jesus Christ, emphasizes the intellectual aspect of formation of conscience, i.e. need for clear and convincing arguments about the value of human life and the proficiency of educating the young generation to live sexually in the service of love and life. It also draws attention to the many signs of the victory of the culture of life, but also to phenomena that point to the need for further actions to defend human life.